1991
DOI: 10.1002/1097-0142(19910215)67:4<1019::aid-cncr2820670426>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile (embryonal and alveolar) rhabdomyosarcoma of the head and neck in adults. A clinical, pathologic, and immunohistochemical study of 12 cases

Abstract: Sites in the head and neck region (orbit, nasopharynx, nasal cavity, etc.) are among the most frequent locations for juvenile (embryonal and alveolar) rhabdomyosarcomas in patients younger than 15 years; however, comparable neoplasms in adults are very uncommon. A clinicopathologic and immunohistochemical study of 12 juvenile rhabdomyosarcomas in patients between the ages of 18 and 36 years is presented. There was a female:male ratio of 2:1. The orbit with or without contiguous paranasal sinus involvement, nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…Most patients with rhabdomyosarcoma are under the age of 25 years, and only a few studies on adult cases have been reported. 3,5 Of 26 patients with rhabdomyosarcoma in the head and neck encountered at UCLA Medical Center, one was 56 years old while all the others were younger than 25 years old. 6 Lloyd et al identified four cases (57%) of rhabdomyosarcoma in the head and neck region in a series of 54 cases of embryonal rhabdomyosarcomas in adults, but there was no case of a tumor in the cervical region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with rhabdomyosarcoma are under the age of 25 years, and only a few studies on adult cases have been reported. 3,5 Of 26 patients with rhabdomyosarcoma in the head and neck encountered at UCLA Medical Center, one was 56 years old while all the others were younger than 25 years old. 6 Lloyd et al identified four cases (57%) of rhabdomyosarcoma in the head and neck region in a series of 54 cases of embryonal rhabdomyosarcomas in adults, but there was no case of a tumor in the cervical region.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Moreover, rhabdomyosarcomas tend to have more aggressive behavior in adults than in children. 3,5 The overall prognosis for patients with rhabdomyosarcoma has improved since the introduction of multidisciplinary treatment. 2,14 Using combination chemotherapy and appropriate radiotherapy, patients with tumors confined to the site or organ of origin had a favorable prognosis regardless of surgical resectability.…”
Section: Discussionmentioning
confidence: 99%
“…The standard classification is still the one proposed by Horn and Enterline [7] in 1958 which divided the tumor into four subgroups: embryonal, alveolar, botryoid and pleomorphic and noted that botryoid was actually a subtype of embryonal [6]. There seems to be a discrete age range characterizing RMS, so that embryonal types occur in infants and toddlers, pleomorphic types arise in adults, and alveolar tumors seem to affect all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, this age distribution corresponds to the histologic maturity of the RMS subtype, because embryonal types resemble embryonic tissues and pleomorphic types appear as aggressive adult cancers with malignant fibrous histiocytoma like features. However, exceptions do occur in occasional adults, and tumors with the histology of embryonal RMS or its spindle cell variant are occasionally reported [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Both adult and foetal type rhabdomyomas are more common in males (Agamanolis et al, 1986;Kapadia et al, 1993). Recently a juvenile-type of rhabdomyoma has been described which appears as an intermediate form between the foetal-and adult-type (Nakheh et a l 1991;Crotty et a l, 1993). Microscopically intracranial rhabdomyomas must be distinguished from rhabdomyosarcomas, medullomyoblas-…”
Section: Discussionmentioning
confidence: 99%